Cancer (mantis) digitalis herbst, 1793, an objective synonym of oratosquillina quinquedentata (brooks, 1886): Neotype designation and reversal of precedence (crustacea: Stomatopoda: Squillidae) - Ahyong, S.T. (2014)
10.11646/zootaxa.3691.5.6